2016
DOI: 10.1057/bm.2016.6
|View full text |Cite
|
Sign up to set email alerts
|

Toward a model of brand strategy adoption

Abstract: Before starting her academic career, she worked over 15 years in field of international marketing in family-owned SME and as brand manager in consumer-goods enterprise. She is currently member of editorial board of Finnish Business Review and a reviewer in International Journal of Management and Enterprise Development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In spite of the burgeoning state of branding studies, however, three key deficiencies are observed in marketing literature. First, a significant gap exists regarding the amount of branding research focusing on small-and medium-sized enterprises (SMEs) in comparison with those carried out with large organizations settings (Neuvonen, 2016). Second, the branding literature exhibits a paucity of research works emanating from emerging or less-developed economies compared to those from developed economic settings (Odoom, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the burgeoning state of branding studies, however, three key deficiencies are observed in marketing literature. First, a significant gap exists regarding the amount of branding research focusing on small-and medium-sized enterprises (SMEs) in comparison with those carried out with large organizations settings (Neuvonen, 2016). Second, the branding literature exhibits a paucity of research works emanating from emerging or less-developed economies compared to those from developed economic settings (Odoom, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…BI allows a firm to own the innovation and generate a longer-lasting source of differentiation, as the brand enhances its visibility, communicates its features and benefits and adds credibility and legitimacy to the innovation (Aaker, 2007). In fact, innovation mediates the influence of the distinctiveness of a brand (Auh and Shih, 2009; Neuvonen, 2016; Wong and Merrilees, 2008). Further, a branded innovation can even have a positive carryover effect on the perception of a corporate/parent brand (Aaker, 2007; Brexendorf et al , 2015; Jensen and Beckmann, 2009) – case in point, what the iPod and iPhone did for Apple.…”
Section: Brandingmentioning
confidence: 99%
“…To answer this question, this paper integrates the literature on BI (Aaker, 2007; Ambler and Styles, 1997; Auh and Shih, 2009; Beverland et al , 2010, 2015; Brexendorf et al , 2015; Clayton and Turner, 1998; Jensen and Beckmann, 2009; Keller and Lehmann, 2006; Nedegaard and Gyrd-Jones, 2013; Neuvonen, 2016; O'Cass and Ngo, 2007), organizational ambidexterity (Birkinshaw and Gupta, 2013; Cao et al , 2009; Hughes, 2018; Josephson et al , 2016; Lee et al , 2016; Levinthal and March, 1993; March, 1991; Raisch and Birkinshaw, 2008; Swift, 2016) and resource/knowledge-based view of firms (Barney, 1991, 1995; Cohen and Levinthal, 1990; Kogut, 1988; Levinthal and March, 1993) and proposes a strategic typology that considers exploitation and exploration as the two strategic underlying orientations that determine the degree of BI efforts made by a firm. This paper takes the stance that branding efforts are anchored in exploitation orientation – with a focus on selection, refinement, efficiency enhancement and the implementation of existing resources and competencies – whereas innovation efforts are anchored in exploration orientation – which includes activities such as search, variation, experimentation and discovery to develop new resources and competencies (Cao et al , 2009; March, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the burgeoning state of branding studies, however, three key deficiencies are observed in marketing literature. First, a significant gap exists regarding the amount of branding research focusing on small-and medium-sized enterprises (SMEs) in comparison with those carried out with large organizations settings [30]. Second, the branding literature exhibits a paucity of research works emanating from emerging or less-developed economies compared to those from developed economic settings [31].…”
Section: Literature Reviewmentioning
confidence: 99%